Who Is El Ángel (1961-1995)? Poetry and Life on the Wild Side about Spanish Transition to Democracy (XXI Century. Spanish Literature and Culture, 2017)
What we are trying to draw here is a union between life and written work, to present an unknown poet and musician of the spanish transition, El Ángel (1961-1995). We focus on reviewing his life experience and his society as keys to understanding his poems. A life of risk and transgression, on a journey through drugs, heroin, love, disease or punk and rock. This poet defies the official discourse of his time on democracy, the eighties movida and culture, to place himself consciously in the margin, counterculture, subculture, and self-destruction.
Keywords: poetry; Life-written work; Spanish Transition; Counterculture; drugs; poetryEl Ángel